Antimicrobial Activity of Three Plant Species from the Cañada Region in Oaxaca State Against Bacteria Responsible for Foodborne Diseases - Montiel, Lucio González; Vera, Norma Güemes; Simental, Sergio Soto; Pastelin, Jesús M. Campos (International Journal For Research In Agricultural And Food Science, 2019)
Consumers nowadays expect food to be nutritious, organoleptically attractive, quick and easy to prepare, as well as safe to eat. However, many foods and drinking water represent risks to public health, mainly due to the presence of pathogenic microorganisms, toxins, pesticides or dangerous substances responsible for foodborne diseases (FD). In the present study, the antibacterial activity of hexane, dichloromethane and methanolic extracts of three plant species collected in the Cañada region, in the state of Oaxaca, Mexico was evaluated: Philodendron sp., Sideroxylon palmeri and Verbesina crocata, which are traditionally used in the treatment of gastrointestinal diseases as well as digestive and inflammatory disorders. The antibacterial activity was evaluated against Escherichia coli, E. coli ATCC 8739, Salmonella typhimurium, Staphylococcus aureus ATCC 29213, Vibrio cholerae INDRE 206, Vibrio cholerae CDC V12 and Yersinia enterocolitica. The hexane and dichloromethane extracts of Sideroxylon palmeri and the hexane extract of Verbesina crocata showed greater activity against all of the strains evaluated, while none of the Philodendron sp. extracts presented antibacterial activity. It is concluded that these extracts could be used during food preparation or manufacturing as an important source of natural compounds that can prevent or inhibit the growth of bacteria responsible for foodborne diseases.